PENGGUNAAN MINYAK SAFFLOWER (Carthamus tinctorius L) DAN INOSITOL TERHADAP KONSUMSI PAKAN DAN PERTAMBAHAN BOBOT AYAM SENTUL JANTAN - Refriana, Rosita; Ismoyowati, Ismoyowati; Rimbawanto, Efka Aris (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose this research objective was to assess the use of safflower oil and inositol on feed consumption and body weight gain in male Sentul chickens. Materials and Methods. The research material used in this study was 81 male Sentul gray chickens aged 4 weeks, which were kept for 8 weeks. The materials used as treatment were safflower oil (Carthamus tinctorius L) and inositol. The ration is composed of several feed ingredients for corn, bran, fish meal, soybean meal, palm oil, lysine, CaCO3, methionin and topmix. The materials used as treatment were safflower oil and inositol. The method used was experimental with completely randomized design (CRD), which consisted of 9 treatments with 3 replications, each replication consisting of 4 male sentul chickens. The treatments consisted of: R0 = basal feed (0% safflower oil and 0% inositol), R1 = basalt feed + 0.5% safflower oil, R2 = basalt feed + 1% safflower oil, R3 = basalt feed + 0.5 inositol %, R4 = basal feed + 1% inositol, R5 = basal feed + 0.5% safflower oil and 0.5% inositol, R6 = basal feed + 0.5% safflower oil and 1% inositol, R7 = basal feed + 1% safflower oil and 1% inositol, R8 = basal feed + 1% safflower oil and 1% inositol. Results. The results showed that the use of safflower oil and inositol had no significant effect (P> 0.05) on feed consumption and body weight gain in male Sentul Chicken. The average feed consumption of male sentul hens ranged from 3,175,942 ± 322,008 to 3,520,930 ± 69,056 grams / chicken / 8 weeks. The average body weight gain of male sentul hens ranged from 391.67 ± 1.768 to 556.67 ± 0.262 g /chicken / 8 weeks. The addition of safflower oil (Carthamus tinctorius L) and inositol as much as 0,5%- 1% did not increase feed consumption and significantly increased body weight for male Sentul seizures.